Populism and Internationalism, Evangelical Style: An Introduction to the Fall 2019 Issue - Hoover, Dennis R. (The review of faith & international affairs, 2019)
The fall 2019 issue of The Review of Faith & International Affairs is a special issue presenting an interdisciplinary collection of research articles examining interrelationships between populism and internationalism among American evangelicals. The issue features highly distinguished contributors presenting original data analyses and case studies exploring two sharply contrasting narratives of contemporary evangelical politics. One pictures evangelicals as right-wing anti-globalist populists, while the other pictures them as humanitarian internationalists with increasingly cosmopolitan perspectives.